Effects of groundnut haulms supplementation on intake, digestibility and growth performance of rams (2012)
In the tropics, supplementation of Cynodon nlemfuensis hay with groundnut haulms improves the nutritional value of the hay thereby promoting live weight of rams during the dry season. The objective of this study was to develop a supplementation strategy for dry season when ruminant feeds are inadequate and growth in ruminants is staggared. For 70 d, effects of groundnut haulms supplementation on hay intake and growth performance of rams were assessed, after which digestibility was determined over 14d. Three levels of Cynodon nlemfuensis hay (100, 50 and 0g) and three levels of groundnut haulms (0, 50 and 100g) were described as GHO, GH50 and GH100 respectively. Supplementation had a positive linear effect (P ≤ 0.05) on intake, dry matter (DM) and fibre in GH50 compared to GH0 and GH100 respectively. Similarly, weight gain was highest in GH50 compared to GH0 and GH100 respectively. However, no significant differences (P ≤0.05) were observed among the treatments. It is therefore suggested that, in dry season, it is practical to supplement sheep with 50g/kg Cynodon nlemfuensis hay + 50g/kg groundnut haulm for improved weight gain and nutrient digestibility.